Video Clip and Artiste’s Image as Tools of the Song Hit’s Mediavirus Action Strengthening (Based on the Ukrainian and Russian Compositions of Late 20th – Early 21st Centuries) - Ivanna Shnur (Вісник Київського національного університету культури і мистецтв. Серія: Музичне мистецтво, 2019)
An important place in mass music culture belongs to the song hit – a phenomenon which attributes have not still been explored well finally. Among them – a video clip as a specific form of hit’s incarnation and an artiste’s image as a communicative feature of the phenomenon’s existence. The ascertainment of these aspects is the main objective of the study. The logic of achieving this objective led to the choice such a methodology: the method of analyzing scientific literature on the problem (to determine the degree of its elaboration and the prospect of further exploration), the method of intonation analysis (in the study of the musical language’s features and the principles of composition’s organization), the functional method (aimed at studying the degree of subject’s dependence on audience’s socio-cultural inquiries), the communicative method (that allows take into consideration the factor of the compositions’ existence in the public consciousness, the audience’s reaction to them and artiste’s personality), the comparative method (to study the genre and intonation and also the individual image components of the song hit). The song hit aims to reach the widest possible audience so this fact dues to the presence of such components as a media virus and a meme in its structure. They are directed at appealing to psychological “sensitive points”, the rooting in the mind and the causing of their further distribution, they can be found at all the song hit’s levels and they aim at the comprehensive coverage of the listener/viewer. Results. The song hit’s communicative nature determines the significance of its visual component represented by the video clip. In addition to the representative function, this embodiment is the most effective media virus tool. Moreover, the hit’s promoting, the marketing nature extends to its performer’s competitiveness. This aspect involves the obligatory presence the viral properties in the image, which can cause the audience’s emotional response. The artiste’s representative function necessitates constant and purposeful work on his image.